A Review on Nanotechnology and Its Impact with Challenges on Electrical Engineering - Khan, Md Yakub Ali; Elme, Nafisa Sultana; Tahrim, H M; Raza, Kala (Peneliti Teknologi Teknik Indonesia, 2024)
Nanotechnology has revolutionized the field of electrical engineering, enabling the development of new materials, devices, and systems with unique properties and functionalities. This review article provides an overview of the impact of nanotechnology on electrical engineering, covering various areas such as analogue and digital circuits, power electronics, sensors, and energy harvesting. The article begins by discussing the basics of nanotechnology, Graphene-based Nanotechnology, nanoscience, Nano photonic and its potential impact on electrical engineering. It then focuses on the application of nanotechnology in various fields of electrical engineering, such as the development of high-performance transistors, nanoscale sensors, and efficient energy conversion systems. The article also discusses the challenges associated with the application of nanotechnology in electrical engineering, such as the need for high-precision fabrication techniques, the issue of reliability and reproducibility, and the potential health and environmental concerns. Overall, the review article highlights the immense potential of nanotechnology in electrical engineering and its impact on various fields of research and development. While challenges exist, continued research and development in nanotechnology promise to lead to significant advancements in electrical engineering, enabling the development of more efficient, and sustainable systems and devices.